Pb-free metal oxide-based epoxy resin nanocomposites for radiation protection: Physical evaluation analysis approach - Toni Beth Guatato-Lopez; Alvie Asuncion-Astronomo; Gil Nonato C. Santos (Heliyon)
Exposure to mid-energy radiation poses significant health risks, necessitating the development of effective shielding materials. Traditional lead-based shields, while effective, have significant drawbacks including toxicity and environmental concerns. This study investigates the potential of lead-free epoxy resin nanocomposites, incorporating bismuth oxide, nickel oxide, and cerium oxide, for mid-energy radiation protection. Nanocomposites were fabricated using an open mold casting technique, and their physical properties were characterized via scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analyses. Further morphological analysis was conducted using a compound microscope and image processing software, ImageJ, to investigate the distribution of the particles on the polymer matrix. The radiation shielding effectiveness of the composites was evaluated using Na-22, Cs-137, and Mn-54 gamma sources in a gamma spectroscopy setup in Philippine Nuclear Research Institute. The results revealed that pure epoxy resin exhibited higher attenuation coefficients compared to the modified composites, primarily due to the challenges in achieving uniform dispersion of metal oxides within the polymer matrix. Agglomeration of nickel oxide nanoparticles was particularly noted, leading to reduced shielding performance. Average mass attenuation coefficients obtained in this experimental setup reached up to 0.08-0.1 cm2/g for energy range 500-900 keV. Radiation protection efficiency (RPE) measurements indicated that pure epoxy resin achieved an RPE of approximately 6% across different sources, highlighting its potential for practical applications in medical imaging, industrial radiography, environmental monitoring, and nuclear power plants. This study underscores the importance of nanoparticle dispersion and provides insights into the development of lightweight, lead-free, and efficient radiation shielding materials. Future work should focus on optimizing synthesis methods to improve homogeneity and radiation protection efficacy of polymer-based composites.